Internações psiquiátricas no nordeste brasileiro no período de 2010 a 2020 - Mendonça, Erica da Silva (2021)
The hospital-centered model, based on the social exclusion of people in psychological distress, was historically and widely used in different countries, including Brazil. However, based on experiences, especially with the Second World War, in which the suffering of prisoners in concentration camps and soldiers at war was compared to the suffering of people who lived locked up in asylums, the need for more effective treatment was perceived. towards these people, hence the movement for Psychiatric Reform, which began to think about the treatment of madness from the perspective of rights. This movement began in Brazil in the 1970s and acquired consistency in the following decade with the redemocratization movement that the country was going through. In 2001, Law 10,216, known as the Psychiatric Reform Law, was passed, which redirected the mental health care model and regulated mental health care services and provided for the protection and rights of people in psychological distress. In this scenario, psychiatric hospitals would be used only in crisis situations, as a last resort, after the devices of the psychosocial care network have been exhausted, however, this is not what we see in practical reality, especially in a scenario of setbacks in the field of health policy. mental health in Brazil. In view of this problem, the research had as its object of study the psychiatric hospitalizations in the Brazilian Northeast from 2010 to 2020 and as a general objective: to analyze the psychiatric hospitalizations in the Northeast region of Brazil in this period. Data collection was carried out using data available in the Hospital Information System of the SUS (SIH/SUS) of the Ministry of Health. The research was exploratory, qualitative in nature and had as its method of analysis the historicaldialectical materialism, which made it possible to the analysis of data from its appearance to its essence. Among the results, we highlight the reduction in the total percentage of psychiatric hospitalizations in Brazil by 34.9% in the period from 2010 to 2020. Among the regions of the country, the one that showed the greatest reduction was the Northeast (42.2%), and also presented the greatest CAPS coverage rate per inhabitant (1.84). In 2020, there was a reduction in the number of psychiatric hospitalizations compared to the previous year, a fact that may be related to the beginning of the covid-19 pandemic that we faced during that year and that continues today. With regard to the types of disorders from which hospitalizations derive, 43.7% of them are from schizophrenia and 27.2% from the use of alcohol and other psychoactive substances. Regarding the age group, 46.9% of hospitalizations occurred with people aged between 20 and 39 years; 55.4% are male and in terms of race/color 55.2% are black and brown, 9.6% are white and 31% are unregistered. We found that the anti-asylum struggle must be permanent, even in a scenario of achievements and advances towards the ideal of mental health care that we aim for, as we live and still can live with numerous setbacks and loss of rights, according to each situation and relationships. of power established in society. Furthermore, the many flags of struggle that we know are also highlighted here, as the struggles are transversal and, therefore, issues such as racism, machismo and class prejudice end up reverberating in mental health indicators, showing that the struggle for a society free of asylums also permeates the struggle against the various oppressions that we find in capitalist sociability.